Greblya na bajdarkakh i kanoe - Slautina, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Author makes a state-of-the-art-analysis of this kind of sports (which has 26 disciplines at World and European Championships and 12 at Olympic games) - with special regard to the situiation of the Russians.